(untitled) (PJDOL, 2023)
The emergence of new ODL institutions and keenness of conventional universities to offer online degree programs in higher education predict its popularity. However, the challenge of how to ensure the quality of learning in ODL institutions is also emerging. In this regard, Virtual University of Pakistan (VUP) has nearly developed first ever quality assurance (QA) toolkit at national level specifically applicable to VUP and generally to allODL institutions offering online programs